Afundamentos de tensão em consumidores industriais : uma análise baseada no fator de impacto e na severidade dos eventos considerando os efeitos de faltas elétricas em sistemas de potência - Oliveira, Roger Alves de (2018)
The present work deals with a comparative analysis of IEEE 1564 standardization and Module 8 of Distribution Procedures of the Brazilian Agency of Electrical Regulation, within the scope of voltage sags. For such comparison, a case study of monitoring is performed on an industrial consumer sensitive to the disturbance during 24 months. Additionally, since the main causes of the voltage sags are the electrical faults of the system to which the industry is inserted, the relations between both events are analyzed. From the simultaneity of these contingencies, a unique set of data was obtained through MATLAB R , which allowed the clustering of variables with K-means algorithm through WEKA software. Simultaneous events were also convenient for the validation of a simulation model in ANAFAS software. The results obtained with the application of such methodology allowed to know the impact of the events, to analyze the vulnerability area, to propose mitigations in the power system under study, as well as to validate a simulation model of sags with relative error less than 10 % to more than 70 % of cases.